Cluster initiative in fine chemicals as a case of practical implementation of Triple Helix collaboration for regional economic growth and innovation-driven development - Liana Kobzeva; Evgeny Gribov; Marina Snigireva; Valensiya Raevskaya (Management dynamics in the knowledge economy, 2017)
The authors apply the cluster theory and the Triple Helix model to analyze the situation and challenges of economic and innovation-driven development of Russian regions starting from 2008 using the example of Tomsk region. Referring to the works of the leading researchers, the authors place special emphasis on the theoretical relevant background for the situation of the practical decision-making regarding the development of the regional cluster policy. The ground for singling out in the concept of innovation and industrial clusters makes it possible to raise a question of the search for proper measures to support innovation clusters by the regional government. In addition, it allows noticing the change of roles of universities and research institutes. Having reviewed the most prominent examples of petrochemical cluster creation in the world and analyzed a cluster initiative in the fine chemical industry in Tomsk region, the authors make several suggestions regarding the sustainability of cluster initiatives. An analysis of this phenomenon within the frame of Triple Helix enables discovering new areas of work with cluster initiatives for researchers and experts. Besides, the authors show that a cluster initiative based on the SMEs leading role hastens the changes in regional economic and investment policy and research agenda of universities. On top of that, the article analyzes a number of phenomena within the context of the Triple Helix, including the appearance of keystone people. They are able to glue together disparate elements of the ecosystem and become a base for Triple Helix based initiatives.
2819566-8; 2392-8042; Management dynamics in the knowledge economy; 823675920